MARKETING IN COMMERCIAL BANKS AND ITS SPECIFIC CHARACTERISTICS - Norqulov Habibullo; Khamidov Jaloliddin; Zubaydullayev Mirshodbek (American Journals, 2024)
In this article, the meaning of the concept of marketing and its principles of meeting demand and working with consumers, studying the activities of all commercial banks in our country and introducing additional measures for the implementation of marketing applications, and a number of innovative innovations carried out by world banks, are presented in our republic. various tips to commercial banks are analyzed.
Keywords: Commercial banks, bank marketing, marketing model, financial relations, credit system, marketing evolution, capital market, bank.